2018
DOI: 10.1158/0008-5472.can-17-2405
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Adenosine Regulates Tumor Polyfunctional CD73+CD4+ Effector T Cells Devoid of Immune Checkpoints

Abstract: The production of CD73-derived adenosine (Ado) by Tregs has been proposed as a resistance mechanism to anti-PD-1 therapy in murine tumor models. We reported that human Tregs express the ectonucleotidase CD39, which generates AMP from ATP, but do not express the AMPase CD73. In contrast, CD73 defined a subset of effector CD4 T cells (Teffs) enriched in polyfunctional Th1.17 cells characterized by expression of CXCR3, CCR6, and MDR1, and production of IL17A/IFNγ/IL22/GM-CSF. CD39 Tregs selectively targeted CD73 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 45 publications
6
57
1
Order By: Relevance
“…63 In addition, we showed an enrichment in MDR1-positive cells within CD4 + CD73 + Teff infiltrating breast and ovarian carcinomas (unpublished data) that secrete anti-tumor cytokines (IFNγ, IL-17A, TNFα) ex vivo in the absence of adenosine or ATP/AMP. 62 In addition, we evidenced that this specific subset expresses very low level of inhibitory immune checkpoints like PD-1 and CTLA-4. This highly polyfunctional CD73 + MDR1 + Teff population might therefore be of interest in therapeutic approaches combining MDR1-associated chemotherapy and anti-CD73 targeting therapy to avoid adenosine production and potentiate pro-inflammatory response of this specific subset.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…63 In addition, we showed an enrichment in MDR1-positive cells within CD4 + CD73 + Teff infiltrating breast and ovarian carcinomas (unpublished data) that secrete anti-tumor cytokines (IFNγ, IL-17A, TNFα) ex vivo in the absence of adenosine or ATP/AMP. 62 In addition, we evidenced that this specific subset expresses very low level of inhibitory immune checkpoints like PD-1 and CTLA-4. This highly polyfunctional CD73 + MDR1 + Teff population might therefore be of interest in therapeutic approaches combining MDR1-associated chemotherapy and anti-CD73 targeting therapy to avoid adenosine production and potentiate pro-inflammatory response of this specific subset.…”
Section: Introductionmentioning
confidence: 76%
“…61 Moreover, our team recently characterized, in human, the CD73 + Teff population that is particularly enriched in Th1.17 and expressed higher MDR1 levels than their CD73 neg counterpart. 62 A recent study also suggests that MDR1 is also selectively expressed by Teff bearing the lectin-like receptor CD161. 63 When analyzed in detail, it appears that this CD161 + Rh123 low (as a surrogate marker of MDR1) population has strong Th1.17 characteristics and that its high MDR1 expression could contribute to their long-term life span among virus-specific antigen memory T cell pool.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Extensive research has reported that purinergic signaling is a crucial component of tumor microenvironments (TMEs) with therapeutic potential in solid tumors 8,9 . Purine or pyrimidine nucleotides, such as ATP, ADP, and adenosine in TMA, have been discovered as important signaling molecules that engaged different P1 nucleoside and P2 nucleotide receptors on cancer or stromal cells [10][11][12][13] . The complex network of purinergic signaling events plays a key role in immune escape and accelerated growth of cancer cells, and eventually metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…To further characterize the T cell subpopulations, we analyzed the expression of the adenosine (ADO) producing ectonucleotidases CD39 and CD73, which can define a variety of regulatory cell populations [22,23,30]. CD4 + T h cells of the blood can be divided into three subpopulations based on their expression of CD39 and CD73: (I) CD39 + T reg , (II) activated CD73 + T h cells, and (III) double negative T h cells (Fig.…”
Section: Expression Of the Ectonucleotidases Cd39 And Cd73mentioning
confidence: 99%